Law, Politics, and Finance - Levine, Ross, 1960- 16.04.1960- (The World Bank, 2001)
A country's legal origin—whether British, French, German, or Scandinavian—helps explain the development of its financial institutions today. Legal systems differ in their ability to facilitate private exchanges and to adapt to support new financial and commercial transactions. A country cannot change its legal origin, but it can (with considerable effort) reform its judicial system by emphasizing the rights of outside investors, by providing more certain and efficient contract enforcement, and by creating a legal system that adapts more readily to changing economic conditions. Beck, Demirgüç-Kunt, and Levine assess three established theories about the historical determinants of financial development. They also propose an augmented version of one of these theories. The law and finance view stresses that different legal traditions emphasize to differing degrees the rights of individual investors relative to the state, which has important ramifications for financial development. The dynamic law and finance view augments the law and finance view, stressing that legal traditions also differ in their ability to adapt to changing conditions. The politics and finance view rejects the central role of legal tradition, stressing instead that political factors shape financial development. The endowment view argues that the mortality rates of European settlers as they colonized various parts of the globe influenced the institutions they initially created, which has had enduring effects on institutions today. When initial conditions produced an unfavorable environment for European settlers, colonialists tended to create institutions designed to extract resources expeditiously, not to foster long-run prosperity. The authors' empirical results are most consistent with theories that stress the role of legal tradition.